The Influence of Compensation and Career Development on Employee Performance Mediated by Job Satisfaction at the Demak District Health Office - Adi Saputra; Tristiana Rijanti (Mandalika Institute, 2025)
This research investigates the effect of compensation and career development on employee performance, mediated by job satisfaction, at the Demak Regency Health Office. The study found that compensation has a positive and significant effect on job satisfaction, meaning that higher compensation increases employees' job satisfaction. Similarly, career development positively affects job satisfaction, indicating that better career development opportunities enhance job satisfaction. Furthermore, compensation positively and significantly impacts employee performance, with employees who receive adequate compensation showing better performance. Career development also contributes positively to employee performance by providing opportunities for skill enhancement and career advancement. Job satisfaction was found to have a significant positive impact on performance, demonstrating that satisfied employees are more motivated to deliver high-quality work. Additionally, job satisfaction was shown to mediate the effects of both compensation and career development on performance. This suggests that while compensation and career development directly impact performance, job satisfaction plays a crucial intermediary role in enhancing performance outcomes. These findings emphasize the importance of improving job satisfaction through adequate compensation and career development opportunities to optimize employee performance in the health sector.